Reconfiguring the Soft Operation Field - Eda Yeyman; Ayse Sentürer (Footprint)
The evolution of architecture calls for a redefinition of materialism, urging a departure from deterministic systems towards non-linear causality and systems far from equilibrium. This entails recognising the dissolution of human-inhuman boundaries and advocating for tactile and sensory bodies that initiate metabolic changes by penetrating environments. Isabelle Stengers critiques the tendency to frame thought within pre-existing planes, labelling it as stupidity, and advocates for an architecture that proliferates rather than condemns.